B cells as modulators of HPV+ oropharyngeal cancer in a preclinical model - Galán-Ortíz, Jorge R.; Andino del Valle, Kamila A.; Pérez-Rosario, Abelardo A.; Castañón Pereira, Daniel L.; Díaz-Rivera, Jennifer; Merheb-Finianos, Pamela A.; Dorta-Estremera, Stephanie M. (Frontiers in Oncology, 2023)
Among the different immune cells present within tumors, B cells also infiltrate human papillomavirus-positive (HPV+) oropharyngeal tumors. However, the role of B cells during programmed death-1 (PD-1) blockade in HPV+ oropharyngeal cancer needs to be better defined. By using the preclinical mouse model for HPV+ oropharyngeal cancer (named mEER), we characterized B cells within tumors and determined their functional role in vivo during PD-1 blockade. We determined that treatment naïve tongue-implanted tumors, which we have previously demonstrated to be sensitive to PD-1 blockade, contained high infiltration of CD8+ T cells and low infiltration of B cells whereas flank-implanted tumors, which are resistant to PD-1 blockade, contain a higher frequency of B cells compared to T cells. Moreover, B cell-deficient mice (µMt) and B cell-depleted mice showed a slower tumor growth rate compared to wild-type (WT) mice, and B cell deficiency increased CD8+ T cell infiltration in tumors. When we compared tongue tumor-bearing mice treated with anti-PD-1, we observed that tumors that responded to the therapy contained more T cells and B cells than the ones that did not respond. However, µMt mice treated with PD-1 blockade showed similar tumor growth rates to WT mice. Our data suggest that in untreated mice, B cells have a pro-tumorigenic phenotype potentially affecting T cell infiltration in the tumors. In contrast, B cells are dispensable for PD-1 blockade efficacy. Mechanistic studies are needed to identify novel targets to promote the anti-tumorigenic function and/or suppress the immunosuppressive function of B cells in HPV+ oropharyngeal cancer.